2002
DOI: 10.1046/j.1365-2672.2002.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

Washing and chilling as critical control points in pork slaughter hazard analysis and critical control point (HACCP) systems

Abstract: Aims: The aim of this research was to examine the effects of preslaughter washing, pre-evisceration washing, final carcass washing and chilling on final carcass quality and to evaluate these operations as possible critical control points (CCPs) within a pork slaughter hazard analysis and critical control point (HACCP) system. Methods and Results: This study estimated bacterial numbers (total viable counts) and the incidence of Salmonella at three surface locations (ham, belly and neck) on 60 animals/carcasses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 35 publications
5
59
2
2
Order By: Relevance
“…In a study conducted in a commercial abattoir, Bolton et al (2002) reported an increase in total viable bacterial counts from 3.8 to 4.5 log cfu/cm 2 on carcasses at the refrigeration stage. Another study conducted on poultry carcasses showed that after 9 days of storage, Salmonella loads were slightly reduced (by less than 1 log unit) on carcasses refrigerated at 2 and 6°C whereas in carcasses refrigerated at 8°C Salmonella number increased by 1.5 log units (Jiménez, Tiburzi, Salsi, Moguilevsky, & Pirovani, 2009).…”
Section: Carcass Decontamination Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in a commercial abattoir, Bolton et al (2002) reported an increase in total viable bacterial counts from 3.8 to 4.5 log cfu/cm 2 on carcasses at the refrigeration stage. Another study conducted on poultry carcasses showed that after 9 days of storage, Salmonella loads were slightly reduced (by less than 1 log unit) on carcasses refrigerated at 2 and 6°C whereas in carcasses refrigerated at 8°C Salmonella number increased by 1.5 log units (Jiménez, Tiburzi, Salsi, Moguilevsky, & Pirovani, 2009).…”
Section: Carcass Decontamination Treatmentsmentioning
confidence: 99%
“…Similarly, special attention must also be paid to the training of staff on Good Hygienic Practices as well as on the sanitation of slaughtering equipments particularly knives to minimize the risk of cross contaminations. Bolton et al (2002) recommend sanitizing knives by a two-knife system that consists in the utilization of one knife while the other is being sanitized in hot water at 82°C or above.…”
Section: Eviscerationmentioning
confidence: 99%
“…Furthermore, they undergo a scalding process, which is known to favour the proliferation of microorganisms present on carcasses (Bolton et al, 2002;Borch et al, 1996).…”
Section: Microbiological Quality Of the Retailed Meatmentioning
confidence: 99%
“…The FSA reduction in Enterobacteriaceae counts, ranging from approximately 0.2 to 1.1 log 10 cfu/cm 2 , is less than that achieved in other related studies. Bolton et al (2002) reported a 2.5 log 10 cfu/cm 2 reduction in TVC while Gill and Bryant (1993) obtained a 2 log 10 cfu/cm 2 reduction in E. coli, again on pork carcasses after singeing. Overall, singeing instead of pelt removal should have the effect of eliminating fleece-borne vegetative forms of bacterial pathogens if the surface achieves a sufficiently high temperature.…”
Section: Effect Of Singeingmentioning
confidence: 99%